The Belgic Confession Historical background, contextual meaning, contemporary relevance - Muller, D Francois (Reformed Theology in Africa Series, 2023)
This book investigates the contemporary relevance of the Belgic Confession. The book groups the 37 articles of the Belgic Confession together in order to cover the whole confession in 12 chapters (alongside an introductory chapter). The emphasis of the publication falls on two aspects: (1) providing a scope of contemporary theological, ethical and general issues and possible controversies regarding the content of the Belgic Confession; and (2) formulating ethical perspectives and guidelines from the Belgic Confession that may assist in the building of societies. Where applicable, chapters also discuss the history of the text of the Belgic Confession, the organic unity between the articles of the Belgic Confession, a dogma-historical perspective on the development of the doctrine/content of the Belgic Confession and the relationship between the Belgic Confession and other confessions.